The Effectiveness of Using Nearpod Learning Media on the Public Relations Learning Outcomes of Class XI OTKP SMKN 4 Surabaya - Panduwinata, Lifa; Fatma Az-Zahro, Nida (LPPM STKIP Kusuma Negara, 2024)
This research aims to determine the effectiveness of using Nearpod learning media on the public relations learning outcomes of class XI OTKP students at SMKN 4 Surabaya. This research is a type of quasi-experiment with a Nonequivalent Control Group Design. This research was conducted at SMKN 4 Surabaya with 60 class XI OTKP students. The data collection technique used is a test in the form of a post-test. Based on the prerequisite test, it is known that the data is not normally distributed but homogeneous, so a T-test analysis is then carried out using the Mann-Whitney test. The results of the data analysis show the value of Asymp. Sig (2-tailed) is 0.040 < 0.05, which means H1 is accepted. So, using Nearpod learning media in class is appropriate for effective public relations communication materials.